Sugar : Europe's bittersweet policies (Catholic Institute for International Relations LondonGB, 1994)
Looks at how the European Union came to hold such a dominant position in the world sugar economy, and the consequences for developing countries. Makes proposals on how the European Union might reduce the human suffering caused by its sugar policies in developing countries, while protecting the interests of the African, Caribbean and Pacific (ACP) producers who have benefitted from those policies.
Located in Mr. B. Blake's office